2020
DOI: 10.1113/ep088594
|View full text |Cite
|
Sign up to set email alerts
|

The eye in extreme environments

Abstract: Much is known about the physiology and anatomy of the eye. Much less is known about the impact of different environments on the eye, and yet it is the pathophysiology that results from this interaction that is often the precursor to disaster. The present review focuses on the effect of different extreme environments on the visual system; in particular, the way in which such environments affect the sensory mechanism of that system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Most commonly, these hypoxia-induced vision changes are not clinically important and are reversed within weeks upon return to normoxia. Similarly, vasodilation of retinal vessels is reversible when adequate oxygen availability is restored (Bosch et al, 2009;Jaki Mekjavic et al, 2021). Visual function tests were not performed in the present study, however, no apparent hypoxia-related effects on vision were observed or reported by the participants, most likely due to low levels of hypoxia.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Most commonly, these hypoxia-induced vision changes are not clinically important and are reversed within weeks upon return to normoxia. Similarly, vasodilation of retinal vessels is reversible when adequate oxygen availability is restored (Bosch et al, 2009;Jaki Mekjavic et al, 2021). Visual function tests were not performed in the present study, however, no apparent hypoxia-related effects on vision were observed or reported by the participants, most likely due to low levels of hypoxia.…”
Section: Discussionmentioning
confidence: 62%
“…Technological developments (chairlifts and cable cars) have made many highaltitude (≥3,000 m; please see Table 1) ski slopes easily accessible to all levels of skiers, including children (Meijer and Jean, 2008;Giesenhagen et al, 2019). At these altitudes, several environmental factors, such as cold, ultraviolet radiation, and hypoxia, may significantly impact not only physical performance (Cymerman et al, 1996;Jaki Mekjavic et al, 2021), but other physiological and psychological systems as well. Indeed, impairment of the aerobic performance, resulting from the lower partial pressure of oxygen (PO 2 ) at altitude (Wehrlin and Hallén, 2006), has been observed in both adults and children, with the magnitude of such being similar (Kriemler et al, 2016;Kapus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme weather events (EWEs) (e.g., heatwaves and cold spells) were associated with high morbidity through a range of physiological mechanisms (Kephart et al 2022 ). Extreme heat and cold temperatures also affect the structure and function of the eye and vision (Jaki Mekjavic et al 2021 ). It is possible that extreme temperatures and continued exposure to air pollution place additional burdens on eye health.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major, as yet unsolved, problems to be faced by those exposed to long periods of microgravity is the visual disturbances collectively known as space flight‐associated neuro‐ocular syndrome (SANS). Jaki Mekjavic and colleagues discuss this and many other areas in their comprehensive review of the eye in extreme environments (Jaki Mekjavic, Tipton, & Mekjavic, 2021). Planetary habitation is an important aspect of space research dealing with the impact of prolonged exposure to ambient conditions (reduced gravity and oxygen levels) that differ from those of Earth.…”
mentioning
confidence: 99%